A chromosome‐level genome assembly of the giant grouper (Epinephelus lanceolatus) provides insights into its innate immunity and rapid growth. (25th July 2019) - Zhou, Qian; Gao, Haoyang; Zhang, Yong; Fan, Guangyi; Xu, Hao; Zhai, Jieming; Xu, Wenteng; Chen, Zhangfan; Zhang, He; Liu, Shanshan; Niu, Yipeng; Li, Wensheng; et al.
Abstract: The giant grouper ( Epinephelus lanceolatus ) is the largest coral reef teleost, with a native range that spans temperate and tropical waters in the Pacific and the Indian Oceans. It is cultured artificially and used as a breeding species in aquaculture due to its rapid growth rate. Here we report a giant grouper genome assembled at the chromosome scale from sequences generated using Illumina and high‐throughput chromatin conformation capture (Hi‐C) technology. The assembly comprised 1.086 Gb, with 98.4% of the scaffold sequences anchored into 24 chromosomes. The contig and scaffold N50 values were 119.9 kb and 46.2 Mb, respectively. The assembly is of high integrity, including 96.4% universal single‐copy orthologues based on BUSCO analysis. Through chromosome‐scale evolution analysis, we identified alignments of six giant grouper chromosomes to three stickleback chromosomes and some of the genes located within the breakpoints of reshuffling events may related to development and growth. From the 24, 718 protein‐coding genes, we found that several gene families related to innate immunity and glycan biosynthesis were significantly expanded in the giant grouper genome compared to other teleost genomes. In addition, we identified several genes related to the hormone signalling pathway and innate immunity that have experienced positive selection or accelerated evolution, implicating their roles in immune defence and fast growth of the species. The high‐quality genome assembly will provide a valuable genomic resource for further biological and evolutionary studies, and useful genomic tools for breeding of the giant grouper.